Decision-making in sport under mental and physical stress - Hepler, T. J. (International Journal of Kinesiology & Sports Science, 2015)
Background: Successful decision-making in sport requires good decisions to be made quickly, but little is understood about the decision process under stress. Objective: The purpose of this study was to compare decision outcomes and the Take the First (TTF) heuristic under conditions of mental, physical, and no stress. Method: Participants (N=112) were divided into 3 stress groups: mental stress (mental serial subtraction), physical stress (running on treadmill at 60-70% of maximum effort), and no stress (counting backwards by 1). Participants were exposed to 30 seconds of stress and then watched a video depicting an offensive situation in basketball requiring them to decide what the player with the ball should do next. Each participant performed 10 trials of the video decision-making task. Results: No differences were found between the 3 stress groups on decision quality, TTF frequency, number of options generated, or quality of first generated option. However, participants in the no stress and physical stress conditions were faster in generating their first option and making their final decision as compared to the mental stress group. Conclusion: Overall, results suggest that mental stress impairs decision speed and that TTF is an ecologically rationale heuristic in dynamic, time-pressured situations.